2017
DOI: 10.2176/nmc.oa.2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Disadvantages of Multi-axis Intraoperative Angiography Unit for Percutaneous Pedicle Screw Placement in the Lumbar Spine

Abstract: We analyzed clinical usefulness of the high resolution imaging system in a hybrid operation room (OR) for posterior lumbar interbody fusion. A total of 17 patients with lumbar spondylolisthesis between February 2014 and August 2016 were included. Multi-axis imaging system in a hybrid OR was used in 12 patients (hybrid OR group); the conventional C-arm fluoroscopy, in 5 patients (C-arm group). The time to confirm the first percutaneous pedicle screw (PPS) angle (hybrid OR, 80 vs C-arm, 249 s; P = 0.0026) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Although the MAU in our institution is not coupled to a navigation system, image resolution of the MAU is markedly higher than that of the C-arm, allowing clear visualization of the shape or margin of the pedicle and the tip of the guidewire, facilitating more accurate screw insertion than that achieved with the C-arm. 15) In the present study, we found that the accuracy of screw insertion in the MAU+ECD group (98.0%) was higher than that in the C-arm group (92.4%). Richter et al reported a high accuracy by combining the MAU and a navigation system during surgery for orthopedic diseases, including spinal disorders.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Although the MAU in our institution is not coupled to a navigation system, image resolution of the MAU is markedly higher than that of the C-arm, allowing clear visualization of the shape or margin of the pedicle and the tip of the guidewire, facilitating more accurate screw insertion than that achieved with the C-arm. 15) In the present study, we found that the accuracy of screw insertion in the MAU+ECD group (98.0%) was higher than that in the C-arm group (92.4%). Richter et al reported a high accuracy by combining the MAU and a navigation system during surgery for orthopedic diseases, including spinal disorders.…”
Section: Discussionmentioning
confidence: 38%
“…In the present study, we used two different types of information-guided intraoperative supporting devices: a multi-axis angiography unit (MAU) (Artis Zeego, VC21-B, Siemens Healthineers) that can capture wide-range, high-resolution, fluoroscopic images and 3D images (which allows creation of CT-like images intraoperatively), 14 , 15) and an electronic conductivity device (ECD) with a cannulated Jamshidi needle (PediGuard; Spine Guard, Paris, France). 16 18) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The CT-like imaging, that is obtained by the multi-axis angiography unit, further enables intraoperative confirmation of the screw position immediately after screwing. 19) Here, we combined these two pieces of equipment and succeeded in obtaining good results.…”
Section: Discussionmentioning
confidence: 99%
“…Results have been reported that the placement accuracy was higher in the Artis zeego group, and the irradiation dose was significantly lower in the C-arm group (462 mGy vs 102 mGy; P = .0013). [20] Approximately 2 times the irradiation dose was indicated in the Artis zeego group. On the contrary, Kageyama et al also compared the irradiation dose and time between the initial 6 cases and the later 6 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation time and dose gradually decreased, indicating a learning curve. [20] Additionally, Kraus et al proposed the low-dose radiation exposure protocol for the spinal surgery with Artis zeego. The reduced dosage protocol can be drastically reduced the irradiation dose in comparison to routine CT and high-dose protocol with Artis zeego, and produced good image quality in the cadaveric study.…”
Section: Discussionmentioning
confidence: 99%